Peran Managerial Ownership dalam Memoderasi Pengaruh Rasio Keuangan Terhadap Financial Distress pada Perusahaan Infrastruktur yang Terdaftar Di Bursa Efek Indonesia Periode 2019-2022 - Nimas Maulidia; Trias Madanika Kusumaningrum (Jurnal Ilmu Manajemen, 2025)
This research determines what can influence financial distress in infrastructure sector companies for 2019-2022. The independent variables used in this research are debt to asset ratio, total asset turnover, and sales growth. In this study, managerial ownership is used as a moderating variable to determine whether it can moderate the relationship between independent variables and financial distress. Using a purposive sampling technique, the sample in this study used 11 infrastructure sector companies listed on the Indonesian stock exchange for the 2019-2022 period. The data analysis techniques used in this research are logistic regression analysis and moderated regression. The results show that the debt-to-asset ratio positively influences financial distress, total asset turnover does not influence financial distress, and the sales growth variable negatively influences financial distress. Then, managerial ownership cannot be a moderating variable in the debt-to-asset ratio, total asset turnover and sales growth variables. The results of this research can be used as a comparison or reference for research on similar topics. The implications of this research refer to the importance of companies in evaluating financial performance through financial ratios to minimize the risk of financial distress.